POLA KOMUNIKASI BUDAYA PENGGUNAAN REMPAH DI BIDANG SEKSUALITAS DALAM LONTAR RUKMINI TATTWA - Ni Luh Dian Suryantini; Ni Made Yuliani; I Gede Suwantana (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2024)
The spices from Indonesia such as pepper, candlenut to nutmeg are mentioned in the Rukmini Tattwa lontar manuscript as a component of the recipe that is said to be potent or effective. In the past, spices were an expensive item. In the ancient text Rukmini Tattwa, it is stated that a woman can return to virginity by using spices. Likewise with men who can increase confidence. This study uses a qualitative approach with the Purposive Sampling method, which is a technique for taking data sources from informants who are considered to know and understand the subject matter being researched the most. Based on this presentation, the relevant theories used are (1) Simulacra Theory from Jean Baudrillard; (2) The Theory of Cultural Identity put forward by Stephen W. Littlejohn; (3) The Theory of Cultural Imperialism by Herb Schiller. The use of spices in the field of sexuality as stated in Lontar Rukmini Tattwa is not only a physical practice but also a complex cultural phenomenon. Apart from being an economic route, it is also a medium for cultural exchange, including in terms of sexuality. Lontar Rukmini Tattwa, a traditional Balinese manuscript, provides insight into the patterns of cultural communication that occurred related to sexuality at that time. With the display perspective method, the cultural communication that occurs is one-way communication. This means that the pattern of cultural communication using the display perspective method is carried out through exhibitions that are quite effective as a cultural communication tool to narrate or convey the content message of Rukmini Tattwa's lontar. Second, the primary communication pattern which shows the delivery of messages through intermediaries. This pattern includes language and body movements to help provide understanding so that there is no shift in meaning between the denotative and connotative meanings of Lontar Rukmini Tattwa. With the theory of simulakra, the pattern of cultural communication that occurs can be understood that the description in Rukmini Tattwa is a hyperbole or strong metaphor, not a scientific fact. The claim that the herb can restore the condition of women to adolescence is more of a reflection of cultural beliefs or myths that have long been developed. So, even though these claims sound real and convincing, it must be realized that this is only part of a simulation that has no scientific basis.